Holistic approaches and advanced technologies in aviation product recycling. Issue 8 (17th August 2021) - Yakovlieva, Anna; Boichenko, Sergii; Kale, Utku; Nagy, András
Abstract : Purpose: The purpose of this study is to analyze existing policies, methods and technologies, which are aimed at the rational and proper handling of decommissioned aviation transport means, determination of the world trends and substantiation of the prospects for implementation of utilization and recycling programs in the aviation industry. This research is devoted to problems of utilization and recycling of decommissioned aircraft and its components: features of proper handling of aviation industry vehicles are considered; the analysis of existing methods and technologies aimed at the rational and correct handling of the end-of-life aircraft is carried out; the necessity of the introduction of the system of complex utilization of aviation equipment is substantiated; the ecological and economic problems connected with the utilization and recycling of aviation vehicles, their units and units are considered; and the relevance and feasibility of introducing recycling programs in the field of aviation industry waste management are substantiated. Design/methodology/approach: Problems of utilization and recycling of decommissioned aircraft and its components are considered in this research. The analysis of existing methods and technologies aimed at the rational and correct handling of the end-of-life aircraft is carried out. In addition to this, the ecological and economic problems connected with the utilization and recycling of aviation vehicles, their units and parts are considered. Moreover, the relevance and feasibility of introducing recycling programs in the field of aviation industry waste management are substantiated. Findings: In this study, the life cycle of aircraft is carried out and analyzed. The existing methodologies and approaches to end-of-life aircraft recycling and utilization are presented in this paper. The experience of the leading organizations in the sphere of decommissioned aircraft recycling, such as Aircraft Fleet Recycling Association and Process for Advanced Management of End-of-Life Aircraft, are considered as well. Environmental and economical benefits to aviation and neighbor industries, arising from the introduction of aircraft recycling systems, are shown. Originality/value: The existing experience of leading companies in the aviation and aircraft recycling industry is accumulated and analyzed to show and propose the general methodology for the development and implementation methodology of end-of-life aircraft recycling and utilization.